Post-adoption response of farmers toward agroforestry based soil and water conservation measures for watershed management in India: FARMERS RESPONSE TO SOIL AND WATER CONSERVATION MEASURES - shekhawat, Ravindra (Annals of Arid Zone, 2024)
In India, various watershed management programmes were initiated with the main emphasis on Soil and Water Conservation (SWC). It was imperative to study the post-adoption response of the farmers to assess the effectiveness of agroforestry based SWC technologies in watershed management. The present study was carried out in selected watersheds located in different agro climatic zones of the India. Standardized structured data collection schedules were developed along with the relevant indices to measure continuity and discontinuity in adoption, observe technological gap and assess diffusion of the SWC technologies. Results revealed that two-third of agroforestry based SWC measures were continuously adopted, while one-third was discontinued by the farmers. Forty six per cent of the agroforestry technologies were continuously adopted with the technological gap. About one-fifth of agroforestry based SWC technologies were also diffused to other farmers. Considerable number of farmers continuously adopted agroforestry SWC technologies with technological gap as well as discontinued them from their fields. This was due to lack of fund, non-availability of labour and requires huge amount of money to repair and maintain these technologies. Therefore, suitable mechanism of fund availability need to be explored for repairing, managing and maintaining agroforestry based SWC technologies that will help in continuous adoption even after withdrawal of public funded watershed development schemes. The paper demonstrates the level of post-adoption behaviour of farmers regarding continued adoption, discontinuance, technological gap and diffusion of agroforestry based soil and water conservation technologies in India.